PENGARUH HARGA, KETENARAN, DAN LABEL HALAL TERHADAP MINAT BELI KONSUMEN PADA RESTORAN HALAL (STUDI KASUS RESTORAN HALAL DI JABODETABEK) - Abdurroziq, Ali; Ismail, Nurizal; Al-Ayubi, Solahuddin (I-Economics, 2024)
The halal food industry has experienced significant growth, particularly in metropolitan areas such as Jabodetabek. Halal restaurants are currently in high demand, not only because of their halal certification but also because they guarantee the cleanliness and healthiness of the food they serve. This research aims to examine the influence of price, reputation, and halal certification on consumer purchase interest in halal restaurants in Jabodetabek. The price variable includes aspects of product price and service price, while the fame variable includes brand reputation and restaurant popularity. The halal label includes consumer confidence in the halal status of the products served by the restaurant.This study uses Structural Equation Modeling (SEM) by distributing questionnaires to 101 residents of Jabodetabek. The results of these questionnaires will be processed using the smartPLS 3 application. The findings of this study indicate that the price variable has a positive Path Coefficient on consumer purchase interest, but it is not statistically significant. Meanwhile, the reputation and halal certification variables have positive Path Coefficients that are statistically significant for consumer purchase interest. Therefore, the analysis results show that the variables of reputation and halal certification have a greater influence on consumer purchase interest compared to the price variable.